A Specific M|G|∞ Queue System Busy Period and Busy Cycle Distributions and Parameters - Ferreira, M. A. M. (arXiv:2211.04447, 2025)
Solving a Riccati equation, induced by the study of the transient behaviour of the MGInf queue system, a collection of service times distributions is determined. For the MGInf queue, which service time distribution is a member of that collection, the busy period and busy cycle probabilistic studies are performed. In extra, the properties of that distributions collection are deduced and presented.